Multi-Component Antioxidative System and Robust Carbohydrate Status, the Essence of Plant Arsenic Tolerance - Monika Kofroňová; Aneta Hrdinová; Petra Mašková; Jana Tremlová; Petr Soudek; Šárka Petrová; Dominik Pinkas; Helena Lipavská (Antioxidants, 2020)
Arsenic (As) contaminates the food chain and decreases agricultural production through impairing plants, particularly due to oxidative stress. To better understand the As tolerance mechanisms, two contrasting tobacco genotypes: As-sensitive Nicotiana sylvestris and As-tolerant N.tabacum, cv. ‘Wisconsin’ were analyzed. The most meaningful differences were found in the carbohydrate status, neglected so far in the As context. In the tolerant genotype, contrary to the sensitive one, net photosynthesis rates and saccharide levels were unaffected by As exposure. Importantly, the total antioxidant capacity was far stronger in the As-tolerant genotype, based on higher antioxidants levels (e.g., phenolics, ascorbate, glutathione) and activities and/or appropriate localizations of antioxidative enzymes, manifested as reverse root/shoot activities in the selected genotypes. Accordingly, malondialdehyde levels, a lipid peroxidation marker, increased only in sensitive tobacco, indicating efficient membrane protection in As-tolerant species. We bring new evidence of the orchestrated action of a broad spectrum of both antioxidant enzymes and molecules essential for As stress coping. For the first time, we propose robust carbohydrate metabolism based on undisturbed photosynthesis to be crucial not only for subsidizing C and energy for defense but also for participating in direct reactive oxygen species (ROS) quenching. The collected data and suggestions can serve as a basis for the selection of plant As phytoremediators or for targeted breeding of tolerant crops.